Effects of Renal Denervation on Sympathetic Activation, Blood Pressure, and Glucose Metabolism in Patients with Resistant Hypertension - Schlaich, Markus P.; Hering, Dagmara; Sobotka, Paul A.; Krum, Henry; Lambert, Gavin W.; Lambert, Elisabeth A.; Esler, Murray D. (Frontiers in Physiology, 2012)
Increased central sympathetic drive is a hallmark of a number of important and common clinical conditions including essential hypertension, insulin resistance, heart failure, and chronic kidney disease. Afferent signalling from the kidney via sensory nerves has been identified as an important contributor and underlying cause of elevated central sympathetic drive, which in turn increases efferent sympathetic outflow to the kidney and other organs crucially involved in cardiovascular control. The resulting effects on renal haemodynamics, sodium and water retention and renin release contribute to the blood pressure rise and other adverse consequences of sustained sympathetic activation and identify the renal nerves as a logical therapeutic target. Recent clinical studies using catheter based radiofrequency ablation technology to achieve functional renal denervation in patients with resistant hypertension have exposed the sympathetic link between these conditions and indicate that this approach may provide a safe and effective treatment alternative for resistant hypertension and its adverse consequences.